Exploring Challenges and Teaching Strategies in The Movie Entitled “Freedom Writers” By Richard Lagravenese - Agitha Mulyadi; Baginda Simaibang; Mulyadi Mulyadi (LPPM Universitas Pahlawan Tuanku Tambusai, Riau, Indonesia, 2022)
This research aimed at exploring the challenges faced by Ms. Gruwell, teaching strategies found in the Freedom Writers movie by Richard LaGravenese and the implication of this movie in relation to English Language Teaching. This research used content analysis method. The source of the data is the movie entitled “Freedom Writers” by Richard LaGravenese. Method of collecting the data is through watching the movie. Then, the data were analyzed through triangulation: movie, interview and book review. The finding of this research showed that there are some challenges faced by Ms. Gruwell in the movie entitled The Freedom Writers such as Racial and social discrimination, Mockery and insults actions, unfriendly behavior or negative stereotyping inside the class, History of gang, and Loyalty that had an effect inside the class. Next, it is also found that the teacher applied various strategies such as cultures differences strategies, the fish bowl, free writing, independent study, information-driven and thought-provoking as well as ethnic additives strategies to create a conducive classroom climate that is useful for the teaching learning process and also encouraged her students to get better achievements. In addition, the implication of teaching are using games, tape recorder or song, switching or changing students’ seating position, journal writing, reading motivation, and class discussion or debate.